PENGARUH MODEL PEMBELAJARAN CONNECTED MATHEMATICS PROJECT (CMP) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Sri Rahmawati Fitriatien; Ibut Priono Leksono; Prayogo Prayogo (Universitas Cokroaminoto Palopo, 2021)
The research was conducted in students’ mathematical problem - solving skills and there are many students who have difficulty learning mathematics. This is due to the teacher - centered learning. Efforts that can be made to the learning process in the classroom can improve students ' problem - solving skills by selecting and using the relevant learning model. One such relevant learning model is the Connected Mathematics Project (CMP) learning model. The research problem was formulized in